El líder de alto potencial (The High-Potential Leader) - Charan, Ram; Willigan, Geri (BookaVivo, 2021)
Set your sights on high-potential leadership and help your organization thrive In today's tumultuous and rapidly evolving business environment, high-potential leaders are in high demand. Do you have the relationship skills, strategic vision, innovation, and determination to thrive as a high-potential leader in your organization? New York Times bestselling author Ram Charan answers that question and helps you get on the fast track to leadership success in this insightful guide. Traditionally, leaders have risen through the ranks based on their cognitive skills, analytical skills, thoroughness, and even perfectionist tendencies, but as modern businesses have moved to a more digitally-driven model, the criteria for leaders have changed. notably. The High Potential Leader explains the modern business climate while highlighting the critical role of relationship building, communication style, commitment, and the ability to motivate and bring out top performance in others, while highlights the critical role that relationship building, communication style, commitment, and the ability to motivate and bring out the best performance in others play in becoming an impactful leader. Whether you're just embarking on your leadership journey or ready to take the leap to the next level of leadership, Charan's real-world lessons and practical advice will help you discover who you are as a leader, chart your path, accelerate your growth and ultimately become the high-potential leader your organization needs to succeed.